2019
DOI: 10.3389/fpsyg.2019.01270
|View full text |Cite
|
Sign up to set email alerts
|

Gratifications for Social Media Use in Entrepreneurship Courses: Learners’ Perspective

Abstract: The purpose of this study is to explore uses and gratifications on social media in entrepreneurship courses from the learners’ perspective. The respondents must have participated in government or private entrepreneurship courses and joined the online group of those courses. Respondents are not college students, but more entrepreneurs, and their multi-attribute makes the research results and explanatory more abundant. A total of 458 valid data was collected. The results of the survey revealed four gratification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 27 publications
1
111
0
Order By: Relevance
“…They become more sensitive to the environment and more sensible of the new entrepreneurial opportunities arising from environmental changes, while also being able to better seize these opportunities. Wu et al (2018), Hou et al (2019), and Wu and Song (2019) revealed that students' motivations to undertake entrepreneurial activities are affected by entrepreneurship education. Bazan et al (2020) posited that entrepreneurship education affects college students' entrepreneurial motivations significantly.…”
Section: Government Policiesmentioning
confidence: 99%
“…They become more sensitive to the environment and more sensible of the new entrepreneurial opportunities arising from environmental changes, while also being able to better seize these opportunities. Wu et al (2018), Hou et al (2019), and Wu and Song (2019) revealed that students' motivations to undertake entrepreneurial activities are affected by entrepreneurship education. Bazan et al (2020) posited that entrepreneurship education affects college students' entrepreneurial motivations significantly.…”
Section: Government Policiesmentioning
confidence: 99%
“…Therefore, when conducting entrepreneurship education for college students, it is recommended that more courses about moral cognition and empathy be added and that well-designed training programs are implemented to foster their attention toward social needs. And teaching through social media is worth recommending, which can help students access more teaching resources about entrepreneurship (Wu and Song, 2019). Besides, a leader rotation system should be considered in campus activities to improve student's sense of responsibility (Jones et al, 2017).…”
Section: Practical Contributionsmentioning
confidence: 99%
“…The concept of positive psychological quality of entrepreneurship, focusing on the college students, analyzes the problems existing in the innovation and entrepreneurship education based on the questionnaire survey and statistical methods. In addition, it integrates it with the internet and the maker education model in a preliminary manner, aiming to give effective suggestions for the implementation of the maker education model and the development of innovation and entrepreneurship education in colleges and universities (Wu and Song, 2019;Yu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%